A descriptive study on the association of facial asymmetry and the supero-inferior position of the left and right condyles among UPCD proper students - Borlagon, Karen Anne R.
Facial symmetry affects a patient's reason for seeking a dentist, diagnosis and treatment planning in the various fields of Dentistry. The supero-inferior position of the condyle is determined by measuring the condyle to the gonion. It is important in the simulation of articulation when mounting the casts on articulators. Having false simulation, affects fabrication of prosthesis and occlusion. Objectives: The study aimed to determine the association between facial asymmetry and the posterior mandibular height of UPCD proper students. Methodology: A vernier caliper was used to measure the supero-inferior position of the left and right condyles. Adobe Photoshop 7 was used to measure the right and left measurements from the midline to the medial canthus, midline to lateral canthus, midline to tragus, midline to lateral alar margin and midline to oral commissure and compare them to the posterior mandibular height. Results: For males, there was no significant difference between the left and right medial canthus, lateral canthus, alar margin, tragus, oral commisures and posterior mandibular height. For females, there was a significant difference between the left and right medial and lateral canthus but no significant difference between the left and right alar margin, tragus, oral commisures and posterior mandibular height. There was no association between the five bilateral anatomical landmarks and posterior mandibular height in females. There was an association between the oral commisures and posterior mandibular height of males. Conclusion: Based on the results, there is no association between facial asymmetry and the superoinferior position of the left and right condyles of UPCD proper students except for the oral commisures and posterior mandibular height of males.